2013
DOI: 10.1177/0333102413498939
|View full text |Cite
|
Sign up to set email alerts
|

The effect of duration post-migraine on visual electrophysiology and visual field performance in people with migraine

Abstract: Dysfunction on clinical tests of vision is common in between migraine attacks; however, the nature of the defect varies between individuals and can change with time. People with migraine show markers of both retinal and/or cortical dysfunction. Abnormal visual field sensitivity does not predict abnormality on electrophysiological testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…A recent report that assessed the effect of migraine on pattern electroretinogram and visual evoked response demonstrated that migraineurs with visual field deficits have electrophysiologic markers of both retinal and cortical dysfunction after a migraine. 4 Given our patient's subjective bilateral scintillating scotoma, the origin of his field defect was most likely cortical. Although the subtle perimetric abnormality in the right eye is merely suggestive of visual field loss, it is not definitive.…”
mentioning
confidence: 88%
“…A recent report that assessed the effect of migraine on pattern electroretinogram and visual evoked response demonstrated that migraineurs with visual field deficits have electrophysiologic markers of both retinal and cortical dysfunction after a migraine. 4 Given our patient's subjective bilateral scintillating scotoma, the origin of his field defect was most likely cortical. Although the subtle perimetric abnormality in the right eye is merely suggestive of visual field loss, it is not definitive.…”
mentioning
confidence: 88%
“…SAP has identified visual field defects in 20e60% of migraine sufferers in between their attacks ( Fig. 1) (De Natale et al, 1993;Dersu et al, 2013;Lewis et al, 1989;McKendrick et al, 2000;Nguyen et al, 2014;Nizankowska et al, 1997). Visual field sensitivity can also be mapped by kinetic perimetry using a similar achromatic but moving target.…”
Section: Visual Field Testsmentioning
confidence: 99%
“…When studies have specifically compared people with migraine to age-matched non-headache controls, substantial numbers of subtle visual field defects (20e50% of migraine participants) are identified (Drummond and Anderson, 1992;McKendrick et al, 2000;Nguyen et al, 2014). While these visual field deficits may not be classified as abnormal using standard clinical criteria based on the perimeter's global indices, this may partially reflect the contamination of the commercial normative dataset with people who have migraine.…”
Section: Visual Field Testsmentioning
confidence: 99%
See 2 more Smart Citations